2012
DOI: 10.1093/mnras/sts389
|View full text |Cite
|
Sign up to set email alerts
|

Surface density of dark matter haloes on galactic and cluster scales

Abstract: In this paper, in the framework of the secondary infall model, the correlation between the central surface density and the halo core radius of galaxy, and cluster of galaxies, dark matter haloes was analyzed, this having recently been studied on a wide range of scales. We used Del Popolo (2009) secondary infall model taking into account ordered and random angular momentum, dynamical friction, and dark matter (DM) adiabatic contraction to calculate the density profile of haloes, and then these profiles are used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 53 publications
11
34
0
Order By: Relevance
“…As a result, we would still have a baryonic induced self similarity for each galaxy, but the similarity parameter (the constant in Equation (4)), which is an acceleration would depend on the galaxy type. Interestingly, Del Popolo et al (2013) found that the acceleration constant estimated by Gentile et al (2009) is correlated to the mass of the galaxy, which would support the fact that the scaling in Equation (3) depends on galaxy type. A direct consequence of this finding is also to support the fact that the nearly universal relations observed for galaxies are due to internal physics within the galaxies, a category to which the baryonic feedback obviously belongs.…”
Section: Synthesis and Conclusionmentioning
confidence: 77%
“…As a result, we would still have a baryonic induced self similarity for each galaxy, but the similarity parameter (the constant in Equation (4)), which is an acceleration would depend on the galaxy type. Interestingly, Del Popolo et al (2013) found that the acceleration constant estimated by Gentile et al (2009) is correlated to the mass of the galaxy, which would support the fact that the scaling in Equation (3) depends on galaxy type. A direct consequence of this finding is also to support the fact that the nearly universal relations observed for galaxies are due to internal physics within the galaxies, a category to which the baryonic feedback obviously belongs.…”
Section: Synthesis and Conclusionmentioning
confidence: 77%
“…This result agrees with empirical observations. 22 For a BDG, the typical value of M dt ∼ 10 13 M ⊙ 23 gives g d0 ≈ 4 × 10 −10 m/s 2 . Since ρ s r s depends on M dt slowly, the actual range of g d0 is very small.…”
Section: 19mentioning
confidence: 96%
“…Here we recall the model used above. First introduced by [17,18], many of its features were developed in [19][20][21], and allowed studies of the density profiles' universality [22,23], of the density profile of galaxies [24][25][26] and clusters [25,27], and of the inner surface-density of galaxies [28].…”
Section: Modelmentioning
confidence: 99%